Pentingkah Kualitas Informasi Akuntansi Pemerintah sebagai Dasar Pengambilan Keputusan? - Khusaini, Musthofa Amin; Fahlevi, Heru; Indayani, Indayani (AFRE (Accounting and Financial Review), 2022)
The Indonesian Central Government’s Financial Reports are continuously improving in quality, but several studies in Indonesia have found that the usefulness of government accounting information for decision making is still low. This study aims to examine the effect of knowledge of government accounting and financial reporting and the use of information and communication technology on the quality of accounting information and its effect on the usefulness of government accounting information. This study also aims to describe how useful government accounting information is for decision making. Data was collected by distributing questionnaires to heads of work units, officials in the financial sector, and staff in the financial sector of central government vertical work units in Banda Aceh City, Sabang City, Aceh Besar District, Pidie District, and Pidie Jaya District. The sample is 229 work units taken randomly from a population of 350 work units. The data was processed using multiple linear regression. The results of the analysis show that knowledge of accounting and financial reporting and the use of information and communication technology have a significant influence on the quality of accounting information. In addition, there is no direct effect of the three variables on the usefulness of accounting information. However, the variables of knowledge about accounting and financial reporting and the use of information technology have an indirect effect on the usefulness of accounting information through accounting quality DOI: https://doi.org/10.26905/afr.v5i2.7807